Dual EGFR and ABL Tyrosine Kinase Inhibitor Treatment in a Patient with Concomitant EGFR-Mutated Lung Adenocarcinoma and BCR-ABL1-Positive CML. (19th March 2020) - Watanabe, Kousuke; Kage, Hidenori; Nagoshi, Saki; Toyama, Kazuhiro; Ohno, Yoshiyuki; Shinozaki-Ushiku, Aya; Nakazaki, Kumi; Suzuki, Hiroshi; Kurokawa, Mineo; Nagase, Takahide
Abstract : Tyrosine kinase inhibitor (TKI) combination is expected to increase in the era of precision medicine. TKI combination may be required to treat double primary cancers, each having a targetable gene, or to treat a single malignancy with multiple targetable genes. Here, we demonstrate the first report of dual EGFR and ABL TKI treatment in a patient with concomitant EGFR-mutated lung adenocarcinoma and BCR-ABL1-positive chronic myeloid leukemia (CML). A 60-year-old man with an 8-year history of CML was diagnosed as advanced EGFR-mutated lung adenocarcinoma. Complete molecular response of CML had been achieved by imatinib, and ABL-TKI had been switched to nilotinib four years previously due to muscle cramps. We discontinued nilotinib and started afatinib. Although partial response of lung adenocarcinoma was achieved, cytogenetic relapse of CML was observed following nilotinib discontinuation. We applied the previously described framework of cytochrome P450 3A4-mediated oral drug-drug interactions and selected gefitinib and nilotinib to treat both malignancies. We effectively and safely administered this combination for seven months. The present report is the first to demonstrate the safety and efficacy of dual EGFR and ABL TKI treatment in a patient with concomitant EGFR-mutated lung adenocarcinoma and CML.